SATIRE AND HUMOR IN URDU PROSE: CLASSICAL AND MODERN TRADITIONS - Dr. Majid Mumtaz; Thamina Mumtaz; Sayad Moshin Ali Bokhari (Journal of Religion and Society, 2024)
Satire and humor have been significant elements in Urdu prose, providing not only entertainment but also a means to critique societal, political, and cultural issues. This study examines the evolution of satire and humor in Urdu prose, focusing on the classical and modern traditions. The classical tradition, exemplified by figures like Siraj-ud-Din Ali Khan Arzu and Mirza Ghalib, used satire as a tool for social and moral reform. Their works often critiqued social norms, political corruption, and the moral decay of society, blending humor with criticism to encourage reflection and change. In contrast, modern Urdu prose, represented by writers such as Saadat Hasan Manto, Qurratulain Hyder, and modern satirists, has shifted towards more direct and often personal critiques of contemporary society. Modern satire often addresses individual and societal flaws, political inefficiency, and the disillusionment of the common people. It is also more focused on using humor as a form of resistance, challenging authority and exposing hypocrisy. This paper explores the transformation in the use of satire and humor, analyzing how these literary devices have adapted to reflect changing social and political realities. It also discusses the role of satire in raising social awareness and provoking thought, examining the impact of both classical and modern traditions on Urdu literature and society. The evolution of satire and humor in Urdu prose highlights its enduring relevance as a tool for social commentary and reform. Keywords: Urdu prose, satire, humor, classical tradition, modern tradition, social critique, literature, societal issues, political commentary, social reform.